(untitled) - Reddy, Junuthula Narasimha (Boca Raton, Florida, 1994)
The book consists of 8 chapters: Chapter 1 describes the varied physical phenomena that may be encoutered within the limits of nonisothermal, incompressible, visvous flows. Chapter 2 intriduces the finite element method by application to a simplified, two-dimentional heat conduction problem. Chapter 3 extends the finite element method to three-dimentions, time dependence, and practical applications in conduction heat transfer. Chapter 4 describes isothermal viscous fluid mechanics formulations. Chapter 5 extends the viscous flow problem to consider convective heat transfer formulations and applications. Chapter 6 covers inelastic non-Newtonian flows and free surface probems. Chapter 7 surveys the complex topic of viscoelastic flow simulation. The last chapter, chapter 8, concludes the text with a survey of several advanced topics, including turbulence modeling
Keywords: finite element method,fluid dynamics,heat transmission; mathematical models,mathematical models